Effectiveness of an osteopathic treatment on the autonomic nervous system: a systematic review of the literature - Verena Rechberger (European Journal of Medical Research, 2019)
Abstract Objective The objective of this systematic review was to evaluate the effectiveness of an osteopathic treatment on the autonomic nervous system (ANS). For this purpose, published primary studies were analysed and critically evaluated. Method To generate this review, 15 electronic databases were systematically searched for studies. Randomized clinical controlled trials (RCT) and clinical controlled trials (CCT) are included in the review and evaluated with appropriate assessment tools (Downs and Black Checklist and the checklist from Kienle and Kiene). Results 23 published studies (10 RCT, 1 clinic multi-centre study, 1 CCT, 5 randomized cross-over studies, 5 randomized pilot studies and 1 single case study) are included in this review. The studies were evaluated with the assessment tools according to their quality. 3 studies are graded as high quality, 11 as moderate and 8 as low-quality studies. Conclusion The included published studies represent a good level of evidence. Due to a small number of subjects and no follow-ups, the methodological quality is rated as moderate. A significant change on the ANS was shown in studies including High-Velocity Low-Amplitude Techniques (HVLAT). No statement could be drawn in studies in which they used cranial osteopathic techniques due to the lack of methodological quality. A significant change on the ANS is shown in the treatment of the suboccipital region. In studies which evaluated the effectiveness of mobilization in the cervical and thoracic region, no statement could be displayed due to a low level of evidence. None of the findings in these studies have given statements if ANS activation takes place in the sympathetic or parasympathetic system.